EFFECTIVE PREVENTION OF HIGH-RISK CERVICAL CANCER AMONG WOMEN IN DEVELOPING COUNTRIES: A CASE-STUDY IN NIGERIA - Omone, Ogbolu Melvin; Lucky, Kenda; Kozlovszky, Miklós (LIFE: International Journal of Health and Life-Sciences, 2020)
There is a surge of morbidity and mortality among women as a result of untreated cases of Cervical Cancer (CC) which is common among women living in underdeveloped and developing countries. The epidemiology of CC revealed that the application of certain combat and operational risk factors of some germane associated with the formation/development of CC can help avoid being infected by the neoplastic disease or the early discovery at an early stage can help mitigate the spread. Hence, some germane high-risk and low-risk factors of the formation of CC in this study were considered to help differentiate infected women from those that are not infected and to create awareness about HPV for effective prevention of CC formation. This study is aimed at predicting and differentiating the group of women with ‘low-risk’ CC from ‘high-risk’ CC among Nigerian women; identification of ‘high-risk’ population. Therefore, some germane and prevalent risk factors such as having sexual intercourse at an early age (early age at sexual debut/first coitus) and the number of sex partners had over a lifetime, and other known low-risk germane such as poor diet and inadequate knowledge about Human Papillomavirus (HPV) and CC were considered; wherewith HPV is considered a predominant risk factor for the occurrence/possibility of CC among the population. A risk-score assessment Human Papillomavirus (HPV) Assessment Test (HAT) tool was used for data collection. Hence, this study is the first to develop a risk-score assessment test tool for HPV and CC awareness in Nigeria